Blueprint: Mini Durian Flesh Separator / Ahmad Azammudin Husaini … [et al.] - Husaini, Ahmad Azammudin; Hazny, Mohamad Haikal; Ismail, Muhammad Hisyam; Mohd Hamdan, Saufinaziha (2021)
The AS2H Enterprise is a new company that will be operated in Malaysia. The name of this company is come out from name of four members on this business. This business consists of four partners that motivate to be a successful entrepreneur. The members are including general manager, Operations manager, marketing manager and financial manager. Our business is located at Batu Caves, Selangor. After doing some research on the business opportunity that available at Batu Caves, we have decided to specify our business in selling our product. Our business will introduce a new product namely Mini Durian Flesh Seperator which is a product that creates for those who love to eat durian cuisine like Tempoyak. We take seriously to make a product that can help people to make durian cuisine quickly and easily without make their hands be smelly. We applied technology knowledge to produce our product. Target market for this product is lover durian in area Batu Caves since population of people is around 7.3 Million in 2017 (Geographical,2018). Medium income users and people in age 30 to 50 will be our target market. We will expand our target market to Klang Valley include Kuala Lumpur, Shah Alam and etc in future